A Novel Drosophila Model of Alzheimer's Disease to Study A? Proteotoxicity in the Digestive Tract. - Elovsson, G.; Klingstedt, T.; Brown, M.; Nilsson, K.P.R.; Brorsson, A.C. (International journal of molecular sciences, 2024)
Amyloid-? (A?) proteotoxicity is associated with Alzheimer's disease (AD) and is caused by protein aggregation, resulting in neuronal damage in the brain. In the search for novel treatments, Drosophila melanogaster has been extensively used to screen for anti-A? proteotoxic agents in studies where toxic A? peptides are expressed in the fly brain. Since drug molecules often are administered orally there is a risk that they fail to reach the brain, due to their inability to cross the brain barrier. To circumvent this problem, we have designed a novel Drosophila model that expresses the A? peptides in the digestive tract. In addition, a built-in apoptotic sensor provides a fluorescent signal from the green fluorescent protein as a response to caspase activity. We found that expressing different variants of A?1-42 resulted in proteotoxic phenotypes such as reduced longevity, aggregate deposition, and the presence of apoptotic cells. Taken together, this gut-based A?-expressing fly model can be used to study the mechanisms behind A? proteotoxicity and to identify different substances that can modify A? proteotoxicity.